2011
DOI: 10.1016/j.bbamcr.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Microglial calcium signal acts as a rapid sensor of single neuron damage in vivo

Abstract: In the healthy adult brain microglia, the main immune-competent cells of the CNS, have a distinct (so-called resting or surveying) phenotype. Resting microglia can only be studied in vivo since any isolation of brain tissue inevitably triggers microglial activation. Here we used in vivo two-photon imaging to obtain a first insight into Ca(2+) signaling in resting cortical microglia. The majority (80%) of microglial cells showed no spontaneous Ca(2+) transients at rest and in conditions of strong neuronal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
193
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(211 citation statements)
references
References 60 publications
14
193
4
Order By: Relevance
“…Previous studies described spontaneous Ca 2+ transients in microglia in vivo [18,19], and these events are similar as the ones described in our study. First, the percentages of 'active' microglia, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous studies described spontaneous Ca 2+ transients in microglia in vivo [18,19], and these events are similar as the ones described in our study. First, the percentages of 'active' microglia, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…those cells that display at least one transient during the recording period, were similar. Eichhoff et al [18] found that around 22% of the microglia of 2-4 months old CX 3 CR1 +/GFP mice were spontaneously active, whereas we found transients in 25.2 ± 4.1% of adult (P60-P70) microglia. Second, rise and decay kinetics of microglial Ca 2+ transients in vitro and in vivo resemble each other and are in the range of 10-13 s [18].…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations